The Epistles of St Peter, St John and St Jude - Mason, A.J.; Plummer, Alfred; Sinclair, W.M.; Ellicott, Charles John, 1819-1905 (London, UK Cassell, 1910)
Includes index.
Also included in vol 8 of A Bible Commentary for English readers / edited by Charles John Ellicott, [which see also]
Keywords: Bible. N.T. Peter -- commentaries; Bible. N.T. Epistles of John -- commentaries; Bible. N.T. Jude -- commentaries